METODE ENTERPRISE ARCHITECTURE PLANNING DALAM SISTEM INFORMASI PENGELOLAAN DATA INVENTARIS - Ahmad Ashifuddin Aqham; Edy Siswanto; Dendy Kurniawan (UNIVERSITAS STEKOM, 2023)
Schools are formal government-owned or private institutions engaged in education, which are held for the community and aim to educate knowledge, self-development, skills and abilities. SMP Negeri 04 Cepiring is the first level educational institution that was established in 1998. So far, school inventory data processing has used MS. Word and MS Excel however, the process takes a long time so it is less effective and efficient. SMP Negeri 04 Cepiring requires an inventory data processing management information system to solve this problem. Inventory data processing information system was built using Enterprise Architecture Planning and using BDMS MySQL as database. The resulting inventory data processing management information system can perform data processing such as entry and exit data, data destruction, mutation or changes that are more accurate.